Analisis Kualitas Pelayanan Dalam Meningkatkan Minat Beli Konsumen Ditinjau Dari Perspektif Etika Bisnis Islam - Anita Sari; Lilis Renfiana (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
Service quality is a strategy that can be implemented to realize desires and hopes so that satisfaction will be created for consumers. If the service quality of a business unit is good, then consumer interest in coming to that place will increase. High consumer buying interest will have a positive impact on business efforts to achieve success. In business, humans are given the freedom to seek maximum profit. However, humans are also bound by ethics so they are not absolutely free in managing and using existing resources. Islam teaches its followers that every business action they take is always guided by Islamic business ethics. This research is descriptive qualitative in nature using interview, documentation and observation data collection techniques. In this case, interviews were conducted with the owner of Ayam Geprek, employees and several consumers. Based on the results of the research and discussion in this thesis, it can be seen that the quality of service provided by Ayam Geprek Agan 24 increases consumer buying interest by 100% for transactional interest, 50% for referral interest, and 0% for preferential interest. Then the quality of service provided by Ayam Geprek 3 Saudara R.A.P increases consumer buying interest by 100% for transactional interest, 40% for referral interest, and 0% for preferential interest. Meanwhile, the quality of service viewed from the perspective of Islamic business ethics at Ayam Geprek Agan 24 is in accordance with the principles of balance/fairness, free will, responsibility and ihsan. However, there is one principle that is not appropriate, namely the principle of unity/tawhid. Then the quality of service is reviewed from the perspective of Islamic business ethics at Ayam Geprek 3 Saudara R.A.P in accordance with the principles of will, responsibility and ihsan. However, according to the principle of balance/fairness, there are still employees who do not comply, such as not smiling and greeting all consumers. Apart from that, the principle that is not in accordance with Islamic business ethics is unity/tawhid.